Neonatal outcomes and risk/benefit ratio of induced multiple pregnancies - Zuppa, A. A. (Journal of medical ethics, 2003)
During recent years we have seen and assisted at a significantly increased number of twin births. The main reason for this increase in the frequency of twin births is the increasing number of so called “induced pregnancies”, whether through hormonal stimulation or artificial insemination techniques.It is well known1 that twins have high mortality and morbidity rates during the perinatal and the following period. The characteristics of conception and pregnancy can determine the development of several pathologies, including prematurity and intrauterine growth retardation, …